1986
DOI: 10.1073/pnas.83.24.9378
|View full text |Cite
|
Sign up to set email alerts
|

Diacylglycerol-induced translocation of diacylglycerol kinase: use of affinity-purified enzyme in a reconstitution system.

Abstract: Diacylglycerol-induced translocation of diacylglycerol kinase (ATP:1,2-diacylglycerol 3-phosphotransferase, EC 2.7.1.107) from the soluble to the membrane-bound compartments was demonstrated both in crude tissue homogenates and in a reconstituted enzyme-membrane model system. In homogenates of either rat brain or liver, incubation with diacylglycerol or phospholipase C, but not phospholipase A2 or phospholipase D, resulted in the translocation of diacylglycerol kinase activity from the soluble to the particula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
2

Year Published

1989
1989
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 32 publications
3
41
2
Order By: Relevance
“…An immunologically and electrophoretically identical isoform of the 80 kDa DAG kinase has been detected in particulate fractions [22]. This may be explained by the report that the 80 kDa DAG kinase translocates to the membrane [16,23,26] or cytoskeleton of cells [8], in response to epidermal growth factor stimulation [26]. It has also been shown that protein kinase C isoforms phosphorylate DAG kinase in itro [26,27].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…An immunologically and electrophoretically identical isoform of the 80 kDa DAG kinase has been detected in particulate fractions [22]. This may be explained by the report that the 80 kDa DAG kinase translocates to the membrane [16,23,26] or cytoskeleton of cells [8], in response to epidermal growth factor stimulation [26]. It has also been shown that protein kinase C isoforms phosphorylate DAG kinase in itro [26,27].…”
Section: Introductionmentioning
confidence: 93%
“…DAG kinase activities have been characterized in rat brain [17,18], baboon brain [19], Drosophila heads [20] and bovine testes [21]. Mammalian DAG kinase activities have been found to be cytosolic [16,18,22], membrane-associated or membranebound [19,[21][22][23], cytoskeletal [8] or nuclear [24]. The first DAG kinase to be purified, characterized and cloned was an 80 kDa protein from pig lymphocyte cytosol [25].…”
Section: Introductionmentioning
confidence: 99%
“…The 80 kDa isozyme requires phospholipids as activators [6,22], and its substrate, diacylglycerol, is believed to be generated in the membrane of agonist-stimulated cells. This raises the possibility that cytosolic DGK is an inactive (or less active) reservoir form.…”
Section: Quantitation Of 80 Kda Dgk By Immunoblottingmentioning
confidence: 99%
“…In the case of DGK, we should consider the fact that the substrate DG is membrane-bound and therefore DGK must bind to the membrane, at least transiently, to reach the substrate. In this regard, DGK was shown to translocate from the cytosol to the membrane in homogenates of rat brain and liver, dependent on the content of membrane-bound DG, although which isozyme is responsible for the translocation remained undetermined (Besterman et al 1986). This suggests that DGK may be partially, if not completely, activated by its own substrate DG and that DGK itself might be one of the targets of a second messenger DG.…”
Section: Subcellular Localization Of Diacylglycerol Kinasementioning
confidence: 99%